MANAJEMEN KEPEMIMPINAN TRANSFORMATIF DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Mukhammad Sobirin; Maghdhuroh, Umi; Rumiyadi, Arif; Joko Prayitno, Harun; Indri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving the quality of education remains a significant challenge for educational institutions in producing graduates who possess academic competence, strong character, and the skills required in the twenty-first century. One of the most influential factors in enhancing educational quality is the leadership of school principals. However, several challenges persist, including low teacher motivation, limited innovation within school culture, and insufficient stakeholder involvement in achieving educational goals. Therefore, a leadership model capable of driving comprehensive organizational change is needed. This study aims to analyze the role of transformational leadership management in improving educational quality and to identify strategies for its implementation within schools. This research employs a library research method using a qualitative descriptive approach. Data were collected through a review of various scientific sources, including books, national and international journal articles, and educational policy documents relevant to transformational leadership and educational quality. The data were analyzed using content analysis techniques. The findings indicate that transformational leadership significantly contributes to educational quality improvement through the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The implementation of transformational leadership enhances teacher professionalism, strengthens a positive school culture, promotes instructional innovation, improves the motivation and performance of educators, and increases parental and community participation. Therefore, transformational leadership management can serve as an effective strategy for developing high-quality, adaptive, and sustainable schools capable of responding to contemporary educational challenges.